Quantifying System Complexity in Design Phase Using Higraph‐Based Models. Issue 1 (13th September 2016) - Aboutaleb, Hycham; Monsuez, Bruno
Abstract: The exponential growing effort, cost and time investment of complex systems in design phase emphasize the need for a methodology, a framework and an environment to handle the system model complexity. For that, it is necessary to be able to measure the system model complexity. This paper highlights the requirements a model needs to fulfill to match human user expectations, presents a generic framework for designing complex systems, and suggests a graph‐based formalism for modeling complex systems. Finally, a way to measure system model structural complexity based on Shannon theory of information is proposed and illustrated with an example.